PEDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN MASJID “NURUL QOLBI” DI DESA WAIHERU KECAMATAN BAGUALA KOTA AMBON - Abdullah Sanduan; Putri Maharani Makatita; Hadijah Kabakoran (Politeknik Negeri Ambon, 2025)
This service aims to assist in preparing financial reports for Nurul Qolbi Mosque using Manual Accounting. The location for this community service activity is at Nurul Qolbi Mosque, behind the Fisheries Science Hall (BIP) in Waiheru Village, Ambon City.The variables in this service project are the assistance in preparing mosque financial reports and the Management of Nurul Qolbi Mosque. The methods for problem-solving implementation include the creation of modules and document formats for simple and practical mosque management, providing guidance in preparing mosque administrative procedures, providing training on preparing financial reports using both manual accounting on computers, and creating simple financial report templates for zakat, infak, and shodaqoh that still meet good accountability requirements.The Community Service Team conducted socialization on program implementation activities and activity evaluation, including the implementation stage, analysis of financial management weaknesses, and preparation of mosque financial reports. Based on the program implementation and activity evaluation results, it was concluded that there was an improvement in the quality of financial management and the preparation of financial reports at Nurul Qolbi Mosque, making them more transparent.Keywords: Financial Report, PSAK 35, Manual Accounting, Nurul Qolbi Mosque Management